Nonfinancial Reporting, Component of Modern Integrated Reporting - Nitu, Cornelia Maria (Journal of Danubian Studies and Research, 2023)
The sustainable development of the business environment requires a permanent connection between it and the community through the lens of social responsibility and environmental issues. Society in general and the business world in particular are used to classical financial reporting, which in principle aimed at a financial accounting analysis of financial performance with the aim, first of all, of complying with certain legal requirements (eg annual financial statements) and secondly of to periodically present the financial achievements to the interested actors (shareholders, investors, partners, authorities and government institutions, etc.), in order to know the results and the real financial position of the companies at a certain moment. Simultaneously with the expansion of multinational companies and the extent of globalization, traditional financial reporting began to give way to non-financial reporting, which, in addition to classic users, is increasingly demanded by employee representatives and members of the communities where these companies operate. As a result, the need for external reporting of information, so-called non-financial, has arisen, which includes the most important aspects regarding: -environment; -attitude and responsibility towards employees; -human rights; - the anti-corruption policy.